2018
DOI: 10.1111/puar.13012
|View full text |Cite
|
Sign up to set email alerts
|

Biased Altruism: Islamophobia and Donor Support for Global Humanitarian Organizations

Abstract: Providing humanitarian assistance to displaced individuals is a critical policy challenge. Many refugee camps are run by charities supported by Western donors. If refugees are predominantly Muslim, might Islamophobia suppress donations to these charities? Using a survey experiment conducted in the United States, the authors examine whether donors' willingness to support a charity is influenced by the dominant religion of the refugees, the regions in which refugee camps are located, and/or the religious affilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…The limits of inclusion are apparent in the unease of many Americans toward members of unusual religious groups and religious newcomers (Bonikowski and DiMaggio 2016; Edgell, Gerteis, and Hartmann 2006; Tremblay‐Boire and Prakash 2019). Anti‐Muslim discourse resonates with many Americans, particularly the more than 30 percent who identify with conservative Protestantism (Pew Research Center 2015) and the quarter of Americans who can be classified as ardent nationalists (Bonikowski and DiMaggio 2016).…”
Section: Judeo‐christian Nationalismmentioning
confidence: 99%
“…The limits of inclusion are apparent in the unease of many Americans toward members of unusual religious groups and religious newcomers (Bonikowski and DiMaggio 2016; Edgell, Gerteis, and Hartmann 2006; Tremblay‐Boire and Prakash 2019). Anti‐Muslim discourse resonates with many Americans, particularly the more than 30 percent who identify with conservative Protestantism (Pew Research Center 2015) and the quarter of Americans who can be classified as ardent nationalists (Bonikowski and DiMaggio 2016).…”
Section: Judeo‐christian Nationalismmentioning
confidence: 99%
“…In a recent study, Bhati (2020) found that implicit color biases play a role in individuals' decisions to donate. Similarly, Tremblay‐Boire and Prakash (2019) found that Christians in America are more likely to contribute to Christian charities operating in the Middle East rather than Muslim charities. Group identity strongly influences decisions to donate toward a group‐specific cause (Hutcheson & Dominguez, 2016; Taniguchi & Thomas, 2011; Wittberg, 2013).…”
Section: Literature Reviewmentioning
confidence: 97%
“…In its extreme version, an emphasis on social identity encourages the “us versus them” attitude where individuals favor members of the in‐group at the expense of others, and even hold prejudices against out‐group members (Tajfel, 1979; Tajfel & Turner, 1986; see also Tremblay‐Boire & Prakash, 2019 for an experiment on the impact of religious in‐group/out‐group identities on charitable giving). However, we are interested in a different, more “positive” aspect of social identity.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Does a cause become less or more worthy if donations are directed toward recipients of certain races, incomes, occupations, immigration status, and so on? Some laboratory and survey experiments have focused on the race/ethnicity, gender, and religion of recipients (Chen et al, 2019; Fong & Luttmer, 2009, 2011; Tremblay‐Boire & Prakash, 2019), but not on immigration status. In this article, we examine whether American donors' willingness to donate to a nonprofit that provides housing and food services to children is affected by the beneficiaries' immigration status and the region from which they came.…”
Section: Introductionmentioning
confidence: 99%